2008
DOI: 10.1016/j.jpedsurg.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Single daily dosing ceftriaxone and metronidazole vs standard triple antibiotic regimen for perforated appendicitis in children: a prospective randomized trial

Abstract: Introduction-Appendicitis is the most common emergency condition in children. Historically, a 3-drug regimen consisting of ampicillin, gentamicin, and clindamycin (AGC) has been used postoperatively for perforated appendicitis. A retrospective review at our institution has found single day dosing of ceftriaxone and metronidazole (CM) to be a more simple and cost-effective antibiotic strategy. Therefore, we performed a prospective, randomized trial to compare efficacy and cost-effectiveness of these 2 regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 19 publications
3
76
0
2
Order By: Relevance
“…This combination has been described as cost-effective. 17 Another important finding of our study shows that fewer children receive suitable treatment than adults, and they consequently develop infectious complications more frequently. As previously shown, children should be treated in the same way as adults until there is no further clinical evidence of infection.…”
Section: Discussionmentioning
confidence: 69%
“…This combination has been described as cost-effective. 17 Another important finding of our study shows that fewer children receive suitable treatment than adults, and they consequently develop infectious complications more frequently. As previously shown, children should be treated in the same way as adults until there is no further clinical evidence of infection.…”
Section: Discussionmentioning
confidence: 69%
“…These patients received a 5-day course of once-a-day dosing of ceftriaxone (50 mg/kg) and metronidazole (30 mg/kg) according to the protocol that was validated in a previous prospective trial [8]. A leukocyte count was drawn on postoperative day 5 in all patients.…”
Section: Protocolmentioning
confidence: 99%
“…Altogether, only a very few studies have demonstrated the clinical benefits and disadvantages of giving postoperative antibiotics along with adequate preoperative antibiotics prophylaxis. 19 The main aim of these prophylactic antibiotics is to lessen the occurrence of postoperative SSIs. 20 Redundant use and continuation of broad-spectrum antibiotics beyond the suggested time period may consequence in inappropriate prophylaxis.…”
Section: Resultsmentioning
confidence: 99%